2023
DOI: 10.3390/ijms24044040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IgE Levels Specific for Ragweed Pollen Extract, Amb a 1 and Cross-Reactive Allergen Molecules

Abstract: Ragweed (Ambrosia artemisiifolia) pollen is a major endemic allergen source responsible for severe allergic manifestations in IgE-sensitized allergic patients. It contains the major allergen Amb a 1 and cross-reactive allergen molecules, such as the cytoskeletal protein profilin, Amb a 8 and calcium-binding allergens Amb a 9 and Amb a 10. To assess the importance of Amb a 1, profilin and calcium-binding allergen, the IgE reactivity profiles of clinically well-characterized 150 ragweed pollen-allergic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For example, it was found that profilin can be a primary airborne sensitizer ( 48 ). According to frequencies of IgE recognition, profilin is an important allergen in ragweed pollen allergy ( 49 ) and in mugwort pollen allergy ( 18 ). For several other allergen sources, profilins were reported to be major allergens such as for eggplant ( 50 ), Amaranthus ( 51 ), melon ( 52 54 ), orange ( 55 ), and oilseed rape ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that profilin can be a primary airborne sensitizer ( 48 ). According to frequencies of IgE recognition, profilin is an important allergen in ragweed pollen allergy ( 49 ) and in mugwort pollen allergy ( 18 ). For several other allergen sources, profilins were reported to be major allergens such as for eggplant ( 50 ), Amaranthus ( 51 ), melon ( 52 54 ), orange ( 55 ), and oilseed rape ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…IgE binding in ImmunoCAP was performed by using commercially available Amb a 1 (w230) and ragweed pollen extract (w1) ImmunoCAPs, whereas rAmb a 6 was first bound to Streptavidin ImmunoCAP (o212, Thermo Fisher Scientific/Phadia, Uppsala, Sweden) as described in [ 19 ]. Specific IgE levels were measured on the Phadia 100 and Phadia 250 platform (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Patients sensitized to ragweed pollen were found to have complex IgE sensitization patterns [ 18 ]. Patients tended to report more symptoms when sensitized to pan-allergens in addition to Amb a 1 [ 18 , 19 ]. Importantly, the allergenic activity of the individual ragweed allergens needs to be evaluated in more detail because the frequency of IgE recognition does not take into consideration this important parameter for the clinical relevance of a given allergen [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rat basophil leukemia (huRBL) RS-ATL8 cells, transfected to express the human high-affinity IgE receptor on their surface [ 29 ], were cultivated and plated, as previously described [ 30 ]. The cells were loaded with 1:10-diluted patient serum from five ragweed-allergic patients, two sensitized to rAmb a 9 (OD ≥ 0.4) and four patients sensitized to rAmb a 10 (OD ≥ 0.4), and incubated overnight at 37 °C, 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%